2022
DOI: 10.3390/ijms23116118
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Long Non-Coding RNAs in Intellectual Disability and Related Neurodevelopmental Disorders

Abstract: In the human brain, long non-coding RNAs (lncRNAs) are widely expressed in an exquisitely temporally and spatially regulated manner, thus suggesting their contribution to normal brain development and their probable involvement in the molecular pathology of neurodevelopmental disorders (NDD). Bypassing the classic protein-centric conception of disease mechanisms, some studies have been conducted to identify and characterize the putative roles of non-coding sequences in the genetic pathogenesis and diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 235 publications
0
3
0
Order By: Relevance
“…LncRNA moesin pseudogene 1, antisense ( MSNP1AS ) may suppress the expression of cytoskeletal protein moesin in the celebral cortex (Liaci et al, 2022; Luo et al, 2020). Moesin is essential for neuronal morphogenesis, immunologic synapse formation and long‐term memory processing.…”
Section: The Impact Of Lncrnas On Actin Polymerization and Progressio...mentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNA moesin pseudogene 1, antisense ( MSNP1AS ) may suppress the expression of cytoskeletal protein moesin in the celebral cortex (Liaci et al, 2022; Luo et al, 2020). Moesin is essential for neuronal morphogenesis, immunologic synapse formation and long‐term memory processing.…”
Section: The Impact Of Lncrnas On Actin Polymerization and Progressio...mentioning
confidence: 99%
“…This cytoskeletal adaptor protein is crucial for maintaining proper actin cytoskeletal rearrangement in brain neurons (Figure 3; Freymuth & Fitzsimons, 2017). Studies indicated that the elevated expression of MSNP1AS may be correlated with the activation of RhoA signalling pathway (Liaci et al, 2022; Luo et al, 2020). Further, RhoA is correlated with Ras superfamily proteins, which are part of same biological signalling pathways, such as actin cytoskeletal integrity, cell proliferation, differentiation, adhesion, migration and apoptosis.…”
Section: The Impact Of Lncrnas On Actin Polymerization and Progressio...mentioning
confidence: 99%
See 1 more Smart Citation